BASHY Dye Platform Enables the Fluorescence Bioimaging of Myelin Debris Phagocytosis by Microglia during Demyelination - Maria V. Pinto (MDPI AG, 2021)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system that is characterized by the presence of demyelinated regions with accumulated myelin lipid debris. Importantly, to allow effective remyelination, such debris must be cleared by microglia. Therefore, the study of microglial activity with sensitive tools is of great interest to better monitor the MS clinical course. Using a boronic acid-based (BASHY) fluorophore, specific for nonpolar lipid aggregates, we aimed to address BASHY’s ability to label nonpolar myelin debris and image myelin clearance in the context of demyelination. Demyelinated ex vivo organotypic cultures (OCSCs) and primary microglia cells were immunostained to evaluate BASHY’s co-localization with myelin debris and also to evaluate BASHY’s specificity for phagocytosing cells. Additionally, mice induced with experimental autoimmune encephalomyelitis (EAE) were injected with BASHY and posteriorly analyzed to evaluate BASHY+ microglia within demyelinated lesions. Indeed, in our in vitro and ex vivo studies, we showed a significant increase in BASHY labeling in demyelinated OCSCs, mostly co-localized with Iba1-expressing amoeboid/phagocytic microglia. Most importantly, BASHY’s presence was also found within demyelinated areas of EAE mice, essentially co-localizing with lesion-associated Iba1+ cells, evidencing BASHY’s potential for the in vivo bioimaging of myelin clearance and myelin-carrying microglia in regions of active demyelination.